Developing a secure and private tele pharmacy platform for remote medication management - Kumar Mire, Sanjay; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
Implementing the e-healthcare paradigm has gained popularity recently throughout different research communities on a global scale. Through the use of contemporary information and communication technology, the e-healthcare solution sends the pertinent patient data to a distant healthcare facility and the relevant medical specialists. Sensitive data access and transmission methods over unprotected channels, however, are dangerous and provide serious security risks. Protecting patient medical information security from unauthorized access or users is crucial, according to standard agencies. Furthermore, studies have shown that identity theft pertaining to medical conditions is a growing and serious crime. Watermarking, steganography, and cryptography are the three methods used to safeguard medical data. Watermarking is the most widely used and promising of these strategies. Hence, medical image data and their dimensionalities are rapidly expanding. Because of these expansions in medical data, manually managing the file system is becoming increasingly challenging. Therefore, the management of medical data has become a major concern for healthcare practitioners. In the medical field, cloud computing is commonly utilised for storing, computing, and exchanging patient medical records. The hospital merely needs to collect patient information from files and upload the data to the cloud for storage via cloud computing.